Arquitetura e recuperação da informação: uma abordagem do Sistema Integrado de Gestão Acadêmica (SIGA) da Universidade Eduardo Mondlane - Macie, Gildo Carlos [UNESP]; Nascimento, Natália Marinho Do [UNESP]; Madio, Telma Campanha De Carvalho [UNESP] (Universidade Federal do Rio Grande do Sul, 2024)
The architecture and retrieval of academic and pedagogical information through the Integrated Academic Management System are addressed with the aim of understanding the efficiency of the system in responding to the demands of students and lecturers at the School of Communication and Arts of the Eduardo Mondlane University (Mozambique), based on the analysis of its architecture. The study is qualitative in its approach and exploratory-descriptive in its objectives, having been operationalized by bibliographic and documentary research for the purposes of theoretical basis, as well as through an approach to the system based on documents that allowed obtaining specific information on the subject in question. It was found that when developing the first versions of the system, little attention was paid to the type of user, the system interfaces were uninviting and the wrong language was used for certain resources, creating dissatisfaction, frustration, or embarrassment for the user to find the desired information to satisfy his or her demands. Furthermore, when the system was used at “peak” times, such as the beginning and at the end of academic semesters, this system was not able to respond to demands with the necessary quality and speed. However, the introduction of this system is considered a great advance for the institution, taking into account the challenges posed by Information and Communication Technologies. The system needs to be continually improved in terms of architecture, in order to increasingly facilitate information retrieval and the inclusion of users with special needs, which is one of the great expectations generated with the implementation of the new version 2.0.

Aborda-se a arquitetura e recuperação da informação acadêmico-pedagógica por meio do Sistema Integrado de Gestão Acadêmica com o objetivo de conhecer a eficiência do sistema na resposta às demandas dos estudantes e docentes da Escola de Comunicação e Artes da Universidade Eduardo Mondlane (Moçambique), a partir da análise da sua arquitetura. O estudo é qualitativo em sua abordagem e exploratório-descritivo em seus objetivos, tendo sido operacionalizado pelas pesquisas bibliográfica e documental para efeitos de embasamento teórico, assim como por meio da abordagem ao sistema a partir de documentos que permitiram obter informações concretas sobre o assunto em pauta. Constatou-se que na elaboração das primeiras versões do sistema, pouca atenção foi dada ao tipo de usuário, as interfaces do sistema eram pouco convidativas e usava-se linguagem equivocada para certos recursos, criando-se insatisfação, frustração ou embaraço ao usuário para encontrar a informação pretendida e satisfazer as suas demandas. Além disso, quando o sistema era usado em tempo de “pico”, como no início e no final dos semestres letivos, este sistema não era capaz de responder às demandas com a qualidade e velocidade necessárias. Contudo, a introdução deste sistema é considerada um grande avanço para a instituição, tendo em conta os desafios impostos pelas Tecnologias de Informação e Comunicação. O sistema precisa ser aperfeiçoado continuamente quanto à arquitetura, no sentido de facilitar cada vez mais a recuperação da informação e a inclusão dos usuários com necessidades especiais, sendo esta, um das grandes expetativas geradas com a implementação da nova versão 2.0.
Architecture and information retrieval: an approach of the Integrated System for Academic Management (SIGA) at Eduardo Mondlane University
Keywords: information; information architecture; information retrieval; SIGA; UEM; informação; arquitetura da informação; recuperação da informação; SIGA; UEM